2019
DOI: 10.1002/ange.201910539
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Encapsulation of Xenon and CH2Cl2 in a Solid‐State Molecular Organometallic Framework (Guest@SMOM)

Abstract: Reversible encapsulation of CH 2 Cl 2 or Xe in anonporous solid-state molecular organometallic framework of [Rh(Cy 2 PCH 2 PCy 2 )(NBD)][BAr F 4 ]occurs in single-crystal to single-crystal transformations.T hese processes are probed by solid-state NMR spectroscopy, including 129 Xe SSNMR. Noncovalent interactions with the -CF 3 groups,a nd hydrophobic channels formed, of [BAr F 4 ] À anions are shown to be important, and thus have similarity to the transport of substrates and products to and from the active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…This is consistent with the H2 accessing the active site at higher temperatures, but not at low temperatures. This observation is reminiscent of work by Weller et al, 37 on Rh based MOFs where Xe gas was found to diffuse away from the active site and reside in hydrophobic pockets, similar to enzymatic gas channels. Further, although the formation of the ion pair clearly showed that H2 had entered the solid at room temperature, our TPD measurements did not detect H2 diffusing out of the lattice after freezing the sample to 77 K and evacuating the surrounding gas.…”
Section: Discussionsupporting
confidence: 68%
“…This is consistent with the H2 accessing the active site at higher temperatures, but not at low temperatures. This observation is reminiscent of work by Weller et al, 37 on Rh based MOFs where Xe gas was found to diffuse away from the active site and reside in hydrophobic pockets, similar to enzymatic gas channels. Further, although the formation of the ion pair clearly showed that H2 had entered the solid at room temperature, our TPD measurements did not detect H2 diffusing out of the lattice after freezing the sample to 77 K and evacuating the surrounding gas.…”
Section: Discussionsupporting
confidence: 68%
“…Variations of the anion, [19,20] chelating phosphine [15,17,21,22] and extension to a paramagnetic Co‐NBA complex [23] have also been reported. The CF 3 ‐groups in the [BAr F 4 ] − anions are also suggested to play an important role in the ingress of gaseous reactants, and the egress of products, through the crystalline lattice, by providing hydrophobic non‐porous channels [24] …”
Section: Introductionmentioning
confidence: 99%